In vitro and in vivo anthelmintic efficacy of plant cysteine proteinases against the rodent gastrointestinal nematode, Trichuris muris - Stepek, Gillian; Lowe, Ann; Buttle, David J.; Duce, I.R.; Behnke, Jerzy M. (Cambridge University Press, 2006)
Extracts of plants, such as papaya, pineapple and fig, are known to be effective at killing intestinal nematodes that inhabit anterior sites in the small intestine, such as Heligmosomoides polygyrus. In this paper, we demonstrate that similar in vitro efficacy also occurs against a rodent nematode of the large intestine, Trichuris muris, and confirm that the cysteine proteinases present in the plant extracts are the active principles. The mechanism of action of these enzymes involved an attack on the structural proteins of the nematode cuticle, which was similar to that observed with H. polygyrus. However, not all plant cysteine proteinases were equally efficacious because actinidain, from the juice of kiwi fruit, had no detrimental effect on either the motility of the worms or the nematode cuticle. Papaya latex was also shown to significantly reduce both worm burden and egg output of mice infected with adult T. muris, demonstrating that enzyme activity survived passage to the caecum and was not completely inactivated by the acidity of the host’s stomach or destroyed by the gastric or pancreatic proteinases. Thus, the cysteine proteinases from plants may be a much-needed alternative to currently available anthelmintic drugs due to their efficacy and novel mode of action against different gastrointestinal nematode species.